2009
DOI: 10.1111/j.1365-2966.2009.15297.x
|View full text |Cite
|
Sign up to set email alerts
|

Linking jet emission and X-ray properties in the peculiar neutron star X-ray binary Circinus X-1

Abstract: We present the results of simultaneous X‐ray and radio observations of the peculiar Z‐type neutron star X‐ray binary Cir X‐1, observed with the Rossi X‐ray Timing Explorer satellite and the Australia Telescope Compact Array in 2000 October and 2002 December. We identify typical Z‐source behaviour in the power density spectra as well as characteristic Z patterns drawn in an X‐ray hardness–intensity diagram. Power spectra typical of bright atoll sources have also been identified at orbital phases after the peria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…Circinus X-1 (Cir X-1) is a confirmed NSXB (Linares et al 2010) known for its regular 16.6 day flares (radio: Whelan et al 1977, IR: Glass 1978, X-ray: Tennant, Fabian & Shafer 1986), believed to be the result of an eccentric orbit (e ∼ 0.40 − 45) (Jonker, Nelemans & Bassa 2007;Johnston, Soria & Gibson 2016) and increased accretion at periastron. Attempts to further classify the system in terms of atoll and Z source behaviour are especially difficult based on its unique X-ray behaviour, with indicators reminiscent of atoll, Z source (Oosterbroek et al 1995;Shirey et al 1998) and even cases which fit neither during phases prior to periastron (Soleri et al 2009b). Cir X-1 also displays relativistic jets, resolved at a variety of scales and wavelengths (X-ray: Heinz et al 2007;Soleri et al 2009a, radio: Stewart et al 1993Fender et al 1998;Tudose et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Circinus X-1 (Cir X-1) is a confirmed NSXB (Linares et al 2010) known for its regular 16.6 day flares (radio: Whelan et al 1977, IR: Glass 1978, X-ray: Tennant, Fabian & Shafer 1986), believed to be the result of an eccentric orbit (e ∼ 0.40 − 45) (Jonker, Nelemans & Bassa 2007;Johnston, Soria & Gibson 2016) and increased accretion at periastron. Attempts to further classify the system in terms of atoll and Z source behaviour are especially difficult based on its unique X-ray behaviour, with indicators reminiscent of atoll, Z source (Oosterbroek et al 1995;Shirey et al 1998) and even cases which fit neither during phases prior to periastron (Soleri et al 2009b). Cir X-1 also displays relativistic jets, resolved at a variety of scales and wavelengths (X-ray: Heinz et al 2007;Soleri et al 2009a, radio: Stewart et al 1993Fender et al 1998;Tudose et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Both NBO and HBO are observed on numerous occasions, but much importance has been given to the timing domain analysis (Cir X-1, Soleri et al 2009;GX 340+0, Penninx et al 1991;GX 17+2, Wijnands et al 1996;Homan et al 2002;Cyg X-2, Wijnands et al 1997;GX 5-1, Dotani 1988). Yu (2007) found HBO and NBO along with twin kHz QPOs in the source Sco X-1 and suggested that NBO resulted from the outward disk movement, but there was no systematic spectral study to support this idea.…”
Section: Introductionmentioning
confidence: 99%
“…Although radio flares from Cir X-1 experienced a long-term lull during that period (Armstrong et al 2013), the source was still active in the radio, with flux densities between a few mJy and a few tens of mJy. Radio emission from the core generally appeared to be present at all orbital phases, but was highly variable and its relation to position along the Z track is not well understood (Soleri et al 2009). While the Chandra and radio data therefore support the possibility of jets and disk winds being present at the same time during the Z source phase of Cir X-1, especially given the presence of a disk wind along the entire Z track of the first Chandra observation in 2000, the case is not as clear as those for GX 13+1 and Sco X-1.…”
Section: Ns Lmxbsmentioning
confidence: 99%